Stability analysis of the milling process of the thin floor structures. (15th February 2022) - Dang, Xue-Bin; Wan, Min; Zhang, Wei-Hong; Yang, Yun
Abstract: Existing studies on analyzing the chatter problem in the milling process of the thin floors only included the dynamic responses of the cutter and the thin floors, however, the static lateral bending defections of the cutter also have actual effect on the stability of the process. This article develops a dynamic model to study the stability of the thin floor milling process by comprehensively considering the multi-flexibilities from both the static bending defections and the dynamic responses. The instantaneous dynamic chip thickness, which is required in the dynamic model, is analytically derived in the three-dimensional space by fully considering the following two factors. One is the bending effect induced by the static and dynamic deflections of the cutter in the X - and Y -directions, and the other is the tensing-compressing effect originated from the dynamic defections of the cutter and the workpiece in the Z -direction. At the same time, based on the substructure and sensitivity analysis theories, the in-situ dynamic parameters of the in-process floor, i.e. the natural frequency and the modal shape, are theoretically formulated by well combining the change of the cutter position with the removal of material. Based on the above derivations, the dynamic cutting forces together with the dynamic governing equation of the milling system are mathematically formulated, and then, the stability of the thin floor milling process is analyzed through solving the critical stability boundary. Finally, a series of milling tests are conducted on a typical thin floor structure to experimentally validate the accuracy and reliability of the proposed model. Highlights: Static defections are included to model the dynamic responses of the thin floor structures. Tensing-compressing effects from both the cutter and the workpiece in Z-direction are considered. An efficient method to capture the workpiece's in-situ dynamical parameters is proposed. Dynamic cutting forces together with stability lobes of the thin-floor milling are formulated. Efficiency and accuracy of the methods are validated by typical thin-floor milling tests.